The apical leakage of mineral trioxide aggregate as the retrograde filling material with various mixing agents - Ema Mulyawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Mineral trioxide aggregate (MTA) is relatively considered as a new material in endodontic. It even has been used as retrograde filling material due to its biocompatibility, antibacterial effect, sealing ability and anti-moist effect. Some materials have been used as mixing agent to achieve an appropiate setting of MTA. Purpose: The aim of this study is to investigate the effect of the mixing agents of MTA towards the apical leakage when they are used together as retrograde filling materials. Method: The samples of this research consist of 30 human extracted upper central incisors. First, the crown of each tooth is sectioned. The root canals are prepared by using the conventional technique and then are obturated with gutta percha. After cutting the root apex, 2 mm from apical, class 1 cavities are prepared by using fissure bur with the depth of 3 mm. The samples then are divided into 3 groups with 10 teeth for each. Group I uses aquabidest as mixing agent of MTA (MTA-aquabidest), group II uses saline (MTA-saline), while group III uses 0.12% chlorhexidine (MTA-chlorhexidine). The apex of each group then is filled with the mixing MTA determined already. Afterwards, clearing method is used to evaluate the apical leakage. The apical leakage actually is determined by measuring the depth of methylene blue penetration with stereomicroscope. The statictical analyses of the linear dye penetration then are performed with analysis of varians ANOVA. Result: The dye penetration for both MTA-aquadest and MTA-saline groups indicates the lowest penetration, and there is even a significant difference compared with MTA-0.12% chlorhexidine group (p<0.005). Conclusion: It can be concluded that aquabidest and saline as mixing agents of MTA produce less apical leakage compared with 0.12% chlorhexidine.Latar belakang: Mineral trioxide aggregate (MTA) merupakan bahan yang relatif baru dalam bidang endodontik. Bahan tersebut diindikasikan sebagai bahan pengisi retrograd karena bersifat biokompatibel, antibakteri, kerapatannya bagus dan tidak terpengaruh kelembaban.Untuk mendapatkan settingnya, beberapa bahan telah digunakan sebagai bahan pencampur MTA. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh bahan pencampur MTA sebagai bahan retrograd terhadap kebocoran apikal. Metode: Bahan penelitian berupa 30 gigi insisivus sentral atas bekas cabutan. Mahkota gigi dipotong dan saluran akar dipreparasi menggunakan teknik konvensional dan diobturasi dengan guta perca. Akar dipotong dengan jarak 2 mm dari apeks dan dibuat preparasi kavitas kelas I menggunakan bur fisura dengan kedalaman 3 mm pada ujung akar tersebut. Akar gigi tersebut dibagi dalam 3 kelompok masing-masing 10. Kelompok I menggunakan akuabides sebagai bahan pencampur MTA (MTA-akuades), kelompok II menggunakan salin (MTA-salin) dan kelompok II menggunakan Chlorhexidine 0,12% (MTA-chlorhexidine). Ujung akar kemudian diisi campuran MTA sesuai kelompoknya. Evaluasi kebocoran apikal menggunakan teknik clearing. Kebocoran apikal ditentukan dengan mengukur kedalaman penetrasi larutan biru metilen menggunakan mikroskopstereo. Hasil pengukuran dianalisis menggunakan analisis varian (ANOVA). Hasil: Penetrasi warna pada kelompok MTA-akuades maupun MTA-salin menunjukkan hasil yang paling kecil dan kedua kelompok tersebut berbeda secara signifikan dengan kelompok MTA-chlorhexidine 0,12% (p<0,005). Kesimpulan: Bahan pencampur akuades dan salin menghasilkan MTA dengan kebocoran apikal yang lebih kecil dibandingkan chlorhexidine.